Book Review: Shiping Tang. 2011. A General Theory of Institutional Change. Issue 2 (December 2019) - Srivastava, Shashi Kant; Srivastava, Khushi
Shiping Tang. 2011. A General Theory of Institutional Change . Routledge, pp. 117, ₹2981.00, ISBN: 978–0–415–59769–2 (hbk), ISBN: 978–0–203–83472–5 (ebk).